SOME REMARKS ON ROUGH STATISTICAL \(Λ\)-CONVERGENCE OF ORDER \(α\) - Antal, Reena; Chawla, Meenakshi; Kumar, Vijay (Ural mathematical journal, 2021)
The main purpose of this work is to define Rough Statistical \(Λ\)-Convergence of order \(α\) \((0<α≤1)\) in normed linear spaces. We have proved some basic properties and also provided some examples to show that this method of convergence is more generalized than the rough statistical convergence. Further, we have shown the results related to statistically \(Λ\)-bounded sets of order \(α\) and sets of rough statistically \(Λ\)-convergent sequences of order \(α\).